INFLUENCE OF NON-PERFORATED SCREEN LOCATION ON HEAT TRANSFER PROCESS IN BUILDING ENCLOSING PARTS - V. D. Sizov; L. V. Nesterov; V. M. Kopko (Наука и техника)
It is recommended to have a vapor-proof barrier on the internal side of heat insulation system in multi-layer building enclosing parts in order to ensure protection of a heat-insulation layer against humidification because relative humidity of internal air is generally higher than external one and diffusion of water steam is directed from premises outside. While having a barrier with high vapor permeability a part of moisture can be accumulated in the structure and heat insulation core and difference of actual and maximum possible partial pressures leads to condensate formation. In order to improve thermal properties of enclosing parts the necessity arises to create a vapor-proof protection screen. It complies with the design of a panel with a vapor-proof screen in the form of non-perforated aluminium foil. The given screen located at internal panel layer prevents penetration of water vapor from premises into enclosing part and heat insulation layer. In such a case condensation zones and, consequently, their moistening can occur in some layers of enclosing parts according to their thermal and physical characteristics. The paper contains a calculation of thermal and moisture regime of the enclosing parts with vapor-proof layer (non-perforated aluminium foil) located in enclosing part core between various layers. An analysis of thermal and moisture regime diagrams for multi-layer external enclosing part demonstrates that the part of non-perforated screen (aluminium foil) located between internal concrete layer and perforated heat insulation layer is considered the most rational one. At the same time other screens between separate layers are perforated.